2013
DOI: 10.1682/jrrd.2012.12.0235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oculomotor rehabilitation on vergence responsivity in mild traumatic brain injury

Abstract: Abstract-A range of dynamic and static vergence responses were evaluated in 12 individuals with mild traumatic brain injury (age: 29 +/-3 yr) having near vision symptoms. All measures were performed in a crossover design before and after oculomotor training (OMT) and placebo (P) training. Following OMT, peak velocity for both convergence and divergence increased significantly. Increased peak velocity was significantly correlated with increased clinically based vergence prism flipper rate. Steady-state response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 62 publications
2
56
0
1
Order By: Relevance
“…[95][96][97] With respect to the treatment of visual symptoms after concussion in adults, a preliminary placebo controlled trial showed that oculomotor training (OMT) therapy improved rhythmicity, accuracy, and sequencing of saccades following mTBI (as a result of oculomotor learning). 98 There was also a significant reduction in near vision-related symptoms, increased visual attention, and improved reading ability in the OMT but not the placebo arm of the study.…”
Section: Cognitive Rehabilitationmentioning
confidence: 87%
“…[95][96][97] With respect to the treatment of visual symptoms after concussion in adults, a preliminary placebo controlled trial showed that oculomotor training (OMT) therapy improved rhythmicity, accuracy, and sequencing of saccades following mTBI (as a result of oculomotor learning). 98 There was also a significant reduction in near vision-related symptoms, increased visual attention, and improved reading ability in the OMT but not the placebo arm of the study.…”
Section: Cognitive Rehabilitationmentioning
confidence: 87%
“…44 Furthermore, research regarding ocular rehabilitation for vergence has demonstrated positive results, namely, an improvement in objective optometric findings, reduction of self-reported symptoms (eg, fatigue, headache), and improvement in function (eg, improved reading). 18,53 Given that impairments in vergence are easily assessed by vision specialists and may be relatively easily correctable with glasses or improved with ocular rehabilitation, 54 further study of the utility of vergence in relation to the clinical identification of mTBI may be worthwhile.…”
Section: Vergence and Accommodationmentioning
confidence: 99%
“…Over 70% of patients with a vertical heterophoria reported relief with prismatic correction [11]. Accommodative symptoms may occur as a result of accommodative insufficiency (incidence of 10-33%), accommodative excess (4%), or varying accommodation [50]. Treatment for accommodative complaints may be addressed with spectacle correction for near.…”
Section: Visual Complaintsmentioning
confidence: 99%
“…Treatment for accommodative complaints may be addressed with spectacle correction for near. Oculomotor training may improve accommodative symptoms in patients with concussion [50], but the improvements may not be sustained after treatment termination [51 & ]. Convergence insufficiency treatments include base in prism, near convergence exercises with in-office or home based programs and oculomotor training.…”
Section: Visual Complaintsmentioning
confidence: 99%
See 1 more Smart Citation